Social Entrepreneurship and Social Innovation in Southeast Asia and its Role on Development: Five Cases and an Innovation Model - Rocha de Sousa, Miguel (2016)
This chapter provides five comprehensive cases of social entrepreneurship and innovation in Southeast Asia and its role on development. We start from a theoretical innovation model based on differential inclusions mathematical theory which is new to the innovation literature. Afterwards we cross-examine the theory with the empirical cases. Main conclusions refer that the differential inclusion model can eventually refer to a more general framework, but nevertheless the five cases are very relevant to specify the use of the model.